Legitimacy of Marriage Dispensation in Religious Courts based on The Law, Judges' Considerations, and Case Decisions - Pasondong, Udin; Fachrurrazy, Muhammad; Yusmad, Muammar Arafat; Beddu, Rahmawati (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2023)
He age limit for marriage in Indonesia has brought changes to the regulation of the marriage age recognized by the state. The previous marriage law (UU No.1/1974) was reformulated into a new policy setting (UU No.16/2019) regarding marriage in Indonesia. This impacts the legitimacy of resolving legal cases of early marriages that occur, whether they are called early marriages, due to changes in statutory provisions or other problems of marrying by accident by taking legal action called marriage dispensation. Existing studies that respond to the issue of marriage dispensation tend to discuss changes or regulations on marriage dispensation after the birth of new regulations, apart from that, existing studies do not consider marriage at an early age as a legal problem that requires careful legal review. To fill this gap, this study focuses on what questions are the factors that cause requests for marriage dispensation, how judges consider making marriage dispensation decisions and a description of the fairness of legal certainty in decisions on marriage dispensation cases. To answer this question, qualitative research was carried out on the statements of judges in religious courts and observing the results of court case decisions to get a comprehensive picture of the application of age regulation in marriage and the reasons why there are requests for marriage dispensation in court. Â From this research it was found that a marriage dispensation is a legal decision made based on the conditions of changes in the age limit in the Marriage Law and the conditions of young couples who are requesting permission to marry. Early marriage factors are caused by various things, data describing family factors, economic factors, and customary factors are the aspects that most influence someone marrying at an early age. The contribution of this research lies in the synchronization between laws, judges' considerations, and case decisions related to marriage dispensations to find harmony between legal norms and social reality.